Patient and health system delay among new pulmonary tuberculosis patients diagnosed at medical college hospitals in Puducherry, India - Natesan, Murugan; Chauhan, Ramesh Chand; Cherian, Johnson; Purty, Anil Jacob; Singh, Zile; Joice, Suba; Abraham, Sherin Billy (International Journal of Research in Medical Sciences, 2017)
Background:Early diagnosis of the disease and prompt initiation of treatment are essential for an effective tuberculosis (TB) control program. The delay in the diagnosis and treatment may worsen the disease, increases the risk of death and enhances tuberculosis transmission in the community. This study was done to assess the extent of various delays and their determinants among TB patients. Methods:A cross-sectional study including retrospective medical record review and patient interviews was conducted during the year 2010 in and around union territory of Puducherry in India. A structured questionnaire used in the WHO multi-country study to estimate the diagnostic and treatment delay in TB was used to interview the patients. Average estimates and proportions were calculated for continuous and categorical variables respectively. Unadjusted odds ratios (OR) were calculated. Level of significance was determined at 95% confidence level (P value <0.05) and all tests applied were two-sided. Results:A total of 138 new sputum smear positive TB patients were included in the study. The mean age of participants was 41.8 years ± 17.3 years (range 15-87 years). Majority (67.4%) of the patients were male and married (68.8%). Majority (86%) of the patients were literate. The median patient delay, health system delay and total delay was 36 days, 28.5 days and 81 days respectively. The place of residence (OR = 0.39, 95% CI = 0.18-0.87) and family size (OR = 0.45, 95% CI = 0.21-0.97) were found as the determinants of various delays for TB patients. Conclusion:Patient and health care system delay for TB patients is long. There is need to improve the referral mechanism to ensure an early initiation of treatment for TB patients diagnosed a tertiary care hospitals.